The changing landscape of Israeli archaeology - Katz, Hayah, author.
1 online resource.
Keywords: "Focused on the connections between archaeology and Israeli society, this book examines the development of Israeli archaeological research, taking historical, sociological, and political contexts into account. Adopting a Foucauldian framework of power and knowledge, the author begins by focusing on archaeological knowledge as a hegemonic discipline, buttressing the national-Zionist identity after the establishment of the State of Israel. The liberalization of political culture in the late 1970s, it is argued, opened the door for a more democratised archaeological discipline. Making use of in-depth interviews with archaeologists belonging to various groups in Israeli society as well as documents from the Israel State Archives (ISA), the book touches on multiple fields of research, including Near Eastern archaeology, religious Jewish society, Israel/Palestine relations and the status of women in Israel. Moreover, although the book deals with the sociology of Israeli archaeology specifically, the author's comparative approach - which highlights the mirroring of social processes and the archaeological discipline - can also be applied to other societies. The book will be of interest to researchers and students in the fields of archaeology, sociology and Israel Studies, as well as to readers with a general interest in the archaeology of the Holy Land"--